Implementasi Kebijakan Sistem Akuntabilitas Kinerja Instansi Pemerintah di Sekretariat Daerah Kota Depok Provinsi Jawa Barat - Darmawaty Darmawaty; Murtir Jeddawi; Sampara Lukman (Institut Pemerintahan Dalam Negeri (IPDN), 2020)
The purpose of this study is directed at to find out and analyze the process of implementing the Government Agency Performance Accountability Policy policies carried out by the Regional Secretariat of the City of Depok. This study used a qualitative research method with a descriptive approach using the theory of Van meter and van horn policy implementation. Data sources obtained from primary data and secondary data. Data Analysis Techniques using the SWOT analysis strategy. The technique of collecting data through interviews, observation and documentation carried out at the Depok City Secretariat, informants as informants in this study include the Mayor of Depok, the Regional Secretary of Depok City, the Head of Section and several Head of Subdivisions at Depok City Secretariat. The results show that the Government Accountability System Policy Implementation Process has not reached the predetermined target due to inaccurate understanding of the substance of the main tasks and functions of measures, targets, policy program objectives of the implementers, lack of budget allocation, inadequate quality of human resources for implementing policies, unavailability of facilities supporting infrastructure, ineffective communication, coordination, limited support for authority and low discipline. Strategies that can be carried out to increase the target and realization of SAKIP by providing intervention and authority support, increasing resources to finance the SAKIP program, increasing the quality and quality of facilities and infrastructure and increasing the quality and professionalism of policy implementers in realizing excellent service.